A typology of professional situations in the analysis of graduate transition from higher education to the labor market - Ramos, Madalena; Parente, Cristina; Santos, Mónica; Chaves, Miguel (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2017)
This article focuses on the Portuguese case to discuss the employment insertion of graduates. It starts by presenting a typology of professional situations with the purpose of analyzing graduate transition from higher education to the labor market. The heuristic potential of the typology is then described, showing its key role when analyzing two important topics in the study of the professional situation of graduates: i) the unequal distribution of individuals in the occupation structure and ii) the relationship between the graduates’ positions in the occupational structure and the work orientations. Two important conclusions are drawn: in Portugal higher education continues to be permeated by reproduction logics of inequalities that go beyond this; the importance of intrinsic and extrinsic values bears almost no relation to variations in levels of job security and material prosperity in this population, for whom intrinsic values are of great relevance.